Synthesis of novel pyrazolyl-selenourea and -carboselenamide molecules for therapeutic applications - Neri-Sierra, Raul Andres (Kansas State University, 2023)
Based on the classical observation that selenium compounds are more biologically active than their sulfur isosteric relatives, the objective of this dissertation is to discuss the synthesis of novel organoselenium compounds containing pyrazolyl selenourea and pyrazolyl carboselenamide motifs. The idea of developing these selenium isomers will be based on the Bossmann’s group staple “NNSN” compounds, which are a family of pyrazolyl carbothioamides and pyrazolyl thioureas that exhibit copper-activated reactivity towards bacterial infections and cancerous murine cells. These compounds will feature a novel NNSeN motif, “NNSeN” pertaining to a structure derived from either a selenourea or carboselenamide featuring a heterocyclic aromatic component with at least one or two nitrogens’ (NNSeN) in the ring, i.e., pyrazoles, and the remaining nitrogen (NNSeN) at the alpha position of the selenoketone (C=Se), or better described as selenourea or selenoamide, functional group. A library of NNSeN compounds were synthesized and their syntheses will be discussed. This dissertation will give insight towards: (i) these novel organoselenium compounds that will generate stable C=Se double bonds (ii) whether these selenium isomers will also chelate copper (I or II) (iii) theoretical studies to understand the geometric orientation and copper complexation of these molecules (iv) preliminary biological studies.
Keywords: Pyrazolyl-selenourea; Pyrazolyl-carboselenamide; NNSeN; Isoselenocyanates; Organoselenium Chemistry